2020
DOI: 10.3389/fcimb.2020.00408
|View full text |Cite
|
Sign up to set email alerts
|

LPG2 Gene Duplication in Leishmania infantum: A Case for CRISPR-Cas9 Gene Editing

Abstract: On the surface of the Leishmania promastigote, phosphoglycans (PG) such as lipophosphoglycan (LPG), proteophosphoglycan (PPG), free phosphoglycan polymers (PGs), and acid phosphatases (sAP), are dominant and contribute to the invasion and survival of Leishmania within the host cell by modulating macrophage signaling and intracellular trafficking. Phosphoglycan synthesis depends on the Golgi GDP-mannose transporter encoded by the LPG2 gene. Aiming to investigate the role of PG-containing molecules in Leishmania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Finally, it was discovered that deletion of LPG2 impairs the result of infection in human neutrophils, as evidenced by an 83 percent reduction in intracellular load compared to wild-type parasite infection. The findings support the role of LPG and other PGs in host-parasite interactions as virulence factors ( 35 ).…”
Section: Introductionsupporting
confidence: 81%
“…Finally, it was discovered that deletion of LPG2 impairs the result of infection in human neutrophils, as evidenced by an 83 percent reduction in intracellular load compared to wild-type parasite infection. The findings support the role of LPG and other PGs in host-parasite interactions as virulence factors ( 35 ).…”
Section: Introductionsupporting
confidence: 81%
“…Following the first successful attempt of gene replacement in L. major ( Cruz et al, 1993 ), genetic manipulation has now been achieved in different leishmania species. Since the recent introduction of CRISPR-Cas9-based methodologies, a significant advance has been made in this field: CRISPR-Cas-9 enabled the deletion of hundreds of genes, including, BTN1 ( Ishemgulova et al, 2018 ) and LeishIF4E-3 ( Shrivastava et al, 2019 ), genes encoding protein kinases ( Baker et al, 2021 ) and flagellar proteins ( Beneke et al, 2019 ) in L. mexicana , as well as LPG2 in L. infantum ( Jesus-Santos et al, 2020 ), RAD51 in L. major ( Damasceno et al, 2020 ) and Ros3 in L. braziliensis ( Espada et al, 2021 ). Herein, we have used the LeishGEdit tool box ( Beneke et al, 2017 ; Beneke and Gluenz, 2019 ) to manipulate the L. braziliensis genome.…”
Section: Introductionmentioning
confidence: 99%
“…The results of their study strengthen the importance of LPG and other PGs as virulence parameters in host-parasite interactions (28). The CRISPR-Cas9 system uniquely enables the simultaneous targeting of multiple genome sites (29).…”
Section: Discussionmentioning
confidence: 71%
“…In this study, con-structed pX-leish was created with three features: (1) Promoters congenial with Leishmania parasites; (2) inserting antibiotic selection marker; (3) all-in-one vector designing, including all components required for CRISPR/Cas9. Also, in a similar study, Jesus-Santos et al in 2020 showed that the deletion of LPG2 impaired the outcome of infection in human neutrophils, as presented by a pronounced diminution (~83%) in intracellular load compared to wildtype parasite infection (28).…”
Section: Discussionmentioning
confidence: 82%